Processo de aprendizagem organizacional em eventos raros: estudo de caso em uma organização privada de educação superior - OLIVEIRA, Alessandro Silva Souza (2012)
This research aimed to contribute to the field of organizational studies by seeking to comprehend how to develop the process of organizational learning through rare events. In this study, the Organizational Learning Process is analysed from an integrated approach, which includes perspectives behavioral, cognitive, social and cultural. In turn, by adopting a procedural perspective, aims understand the influence of rare events by experiencing their, comprising the underlying organizational dynamics. Analyze organizational learning processes, linking them to rare events, is to highlight the processes of change observed in the organizations, from that, understanding the dynamics from which new routines are formed and new knowledge base is created, used and institutionalized. To comprehend the organizational learning process from an integrated approach, it was decided to use as support for the Social Learning Theory (ELKJAER, 2003) and some assumptions of Neoinstitutionalist Theory that are institutionalization and legitimation. To apply these constructs, it was chosen the Brazilian educational sector. This segment is characterized, from 2007, by a high level of competition, professional management and presence of major educational groups in the capital market, which triggered mergers and acquisitions, considered in this study as rare events that allow reveal the Organizational Learning Process in GAMA ALFA, private higher education company, object of this study, which has as acquisition in 2008. Regarding the methodology, the nature of the research was exploratory, and qualitative approach, unique case study method and longitudinal time perspective and cross section in 2011. Data analysis shows that the Learning Process is likely to occur through changes episodic and revolutionary and not only through a continuous and incremental process. In this regard it is noteworthy that the breaks and discontinuities promoted by episodic and revolutionary changes, such as the rare event occurred in ALPHA GAMA can enable a change in the state of knowledge, institutionalizing new routines and practices and deinstitutionalizing others, which is preceded by tension and conflict sources, essential for taking action that enables the reformulation of routines. There was also the important role of technology as artifact material, is able to direct actions for change, crucial to unveil the process of Organizational Learning. Likewise, it highlights also the role of people management routines to create and institutionalize the values and beliefs able to direct the actions of organizational members. Another finding of the research is that learning occurred at the organizational level as they were perceived transformational change or double loop (ARGYRIS AND SCHON, 1978) on the routines of GAMA ALFA, as of which it could be verified the institutionalization of new knowledge, as well as the institutionalization of knowledge into misuse. It was evidenced that the management model and its practices as well as new teaching model were incorporated and stabilized over time, showing that practices and routines have become stabled standard action which represents the incorporation of knowledge.